Alcohol abuse in gastroenterological patients - M. V. Mayevskaya; I. G. Bakulin; A. A. Chirkov; Ye. O. Lyusina; V. D. Lun’Kov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To estimate the role of alcohol abuse in gastroenterological patients. Material and methods. Overall 345 patients with various gastrointestinal diseases were enrolled in the study. Of all patients 162 (46,9%) were males, 183 (53,1%) were females, mean age was 43,18±13,04 years. Patients underwent inquiry by two questionnaires independently: AUDIT-C and CAGE. Gender, age, diagnosis and preferences in the choice of medical specialist were analyzed. Inquiry of doctors was carried out to assess personal experience of interaction with patients. Respondents were proposed to answer a set of questions, concerning frequency of routine application of AUDIT and CAGE questionnaires, carrying out of psychological support of the patient, experience of specific antialcoholic agent prescription in daily practice and interaction with narcologist doctors, satisfaction by obtained knowledge and craving for additional skills of diagnosis and treatment of alcoholism. Results. Of all 345 interrogated patients 49,8% were positive according to AUDIT-C and 45,3% - CAGE questionnaire. Thirty-two percent of patients had liver cirrhosis of toxic and viral etiology, 18% had chronic toxic and viral hepatitis, 11% - non-alcoholic fatty liver disease and various biliary diseases respectively, chronic pancreatitis and chronic gastritis subgroups represented 6% of all patients each, irritable bowel syndrome and gastroesophageal reflux disease - 4% each, primary biliary cirrhosis, hepatocellular carcinoma, stomach and duodenal peptic ulcer disease - 2%. According to doctors opinion strong correlation between between alcohol consumption and disease development was present in 22,2% of men and 8,7% of women. Sensitivity and specificity of questionnaires of AUDIT-C and CAGE was 66 and 91,4%, respectively, diagnostic accuracy - 86,2%, coherence coefficient (Kappa) - 0,567 (medium correlation). Of all patients with alcohol abuse, only 16,5% would refer to attending physician and 10,4% - to narcologist, 8,5% did not consider alcohol consumption as a problem, and 64,4% of them believe that they can cope with the problem on their own. Questioning of doctors indicated that only 35% of them constantly or frequently utilize AUDIT-C and CAGE questionnaires, 25% prescribed specific anti-alcoholic agents and 15% independently initiate anti-alcoholic therapy. However, 65% of physicians actively inquire patients for consumption, and 80% - constantly provide psychological support to patients. Despite that, only 10% of the interrogated doctors were completely satisfied by communication to the patient, and every fourth recognized lack of knowledge and skills in diagnosis and treatment of alcohol abuse. Over a half (60%) of doctors would like to gain additional knowledge in this field. About 50% of doctors recommended patients to address narcologist and only 25% have established contact to them. Conclusion. Development of the follow-up program is required for patients with alcohol consumption issues assisted by professional communities of internist and narcologist doctors. Physicians need to apply screening questionnaires of AUDIT-C and CAGE in their activity, encourage patients to decrease or completely stop alcohol intake, monitor and provide support to patients with alcohol abuse, initiate anti-alcoholic therapy in the cooperation with narcologists that will improve prognosis and decrease mortality from alcohol-related diseases.